Dynamic modeling of hydrogen production from boil-off gas (BOG) at onshore LNG facilities: Technical and socio-economic analysis - Yusuf, Noor (2024)
Integrating hydrogen (H2) production systems within natural gas (NG) supply chains can support smoothening transition to cleaner energy resources by utilizing existing infrastructures. This work investigates the dynamic conversion of boil-off gas (BOG) using steam methane reforming (SMR) to produce H2 within liquified natural gas (LNG) process. The study extends beyond technical considerations to encompass a socio-economic approach, exploring optimal H2 allocation to different monetization techniques (e.g., ammonia and methanol) subject to final market price and demand data. Dynamic simulation showed an excellent ability to address the variations in BOG flow, change in LNG temperature and pressure drop within the LNG supply chain, highlighting the need for adaptive flowrate and process setpoints. The H2 productivity and yield are dependent on steam flow rates, steam to carbon ration (S/C) and energy input to the system. Optimizing the reformer temperature is the best practice to enhanced the conversion of BOG to H2. Allocating approximately 74% of the produced H2 to CO2-free ammonia production, and the remainder to methanol via CO2 hydrogenation, achieves an annual profitability of $1.36 billion. However, when considering variable demand and price data over ten years, the model proposes flexible annual H2 allocation to both monetization routes, resulting in an average yearly profitability of $6.84 billion. These findings underscore the importance of integrating interactive simulation approaches to address exogenous and endogenous uncertainties, providing a robust strategy against risks. The comprehensive approach presented in this study contributes to the understanding and strategic planning of H2 production within LNG supply chains, emphasizing adaptability and economic viability in the dynamic landscape of the energy transition.